Role of Community Based Organization on House Hold Income in Kitumba Sub-County Kabale District. - Niwagaba, Alex (Kabale University, 2024)
The study was about the role of community-based organizations on house hold income in Kitumba sub-county, Kabale District. The study was guided by three objectives which were to learn about the services provided by community-based organizations (CBOs) to the community in the Kitumba sub-county, Kabale district, to determine the effect of CBOs on increased household income in the Kitumba sub-county, Kabale district, to explore the challenges faced by CBOs in the transformation of rural areas in Kitumba sub-county, Kabale district. A targeted population of 80 respondents was considered for the study. These included 01Community Development Officer, 02 parish chiefs, 01 sub-county chiefs, 04 political leaders, 01 health officer, 02 CBO representatives, and 71 community members. Both simple random and purposive sampling techniques were used in identifying the study sample size. The methods that were used in data collection included questionnaires, observation, and interviews. Data collected was edited, coded, entered into the computer, and analyzed with Excel, a Microsoft statistical package, the results were presented in tables. Based on results from the study, 100% of the respondents agreed that there are several services offered by CBOs for the society in the Kitumba sub-county Kabale district they include; Health activities, Environmental management, Children well well-being, Training programs, Education services, Poverty alleviation programs and Community sensitization. The study findings also revealed that there are several effects of CBOs on increased rural incomes in the Kitumba sub-county Kabale district as they include; Economic growth, Evaluation programs, Increased literacy level, Reduced infant mortality rate, Provision of nutritional supplements, Provision of funds to communities and Revenue to the government. The study findings revealed the challenges faced by CBOs in the transformation of rural areas in the Kitumba sub-county Kabale district as they include; Lack of funds, Poor governance, Absence of strategic planning, Poor networking, Poor communication, Limited capacity, and Political interference.